1994
DOI: 10.1007/bf01276429
|View full text |Cite
|
Sign up to set email alerts
|

d-Cycloserine adjuvant therapy to conventional neuroleptic treatment in schizophrenia: an open-label study

Abstract: D-cycloserine, a partial agonist at the strychnine-insensitive glycine site of the NMDA receptor complex, was tested as adjuvant treatment to conventional neuroleptics in chronic schizophrenic volunteers. The drug was administered, o.a.d., at the daily dose of 250 mg for six weeks. Mental status outcome measures were completed at the end of each week of treatment. The major finding was a deterioration of the patients' clinical condition, specifically of their psychotic symptoms. These preliminary results are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 14 publications
2
34
0
1
Order By: Relevance
“…We found that D-cycloserine exacerbated psychotic symptoms in schizophrenia at blood levels 15 times lower (i.e., between 2.0 and 2.9 microgram/ml). The second study reported that 250 mg D-cycloserine daily in addition to conventional antipsychotics aggravated psychotic symptoms in four of seven patients with chronic schizophrenia (Cascella et al 1994). Comparison of this study with our previous report (van Berckel et al 1996) and the only other report currently available in which beneficial effects of D-cycloserine on the negative symptoms of schizophrenia were described (Goff et al 1996) is hampered by differences in design (increasing dosages versus fixed dose), treatment regime (drug-free patients versus patients treated with neuroleptics), and inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that D-cycloserine exacerbated psychotic symptoms in schizophrenia at blood levels 15 times lower (i.e., between 2.0 and 2.9 microgram/ml). The second study reported that 250 mg D-cycloserine daily in addition to conventional antipsychotics aggravated psychotic symptoms in four of seven patients with chronic schizophrenia (Cascella et al 1994). Comparison of this study with our previous report (van Berckel et al 1996) and the only other report currently available in which beneficial effects of D-cycloserine on the negative symptoms of schizophrenia were described (Goff et al 1996) is hampered by differences in design (increasing dosages versus fixed dose), treatment regime (drug-free patients versus patients treated with neuroleptics), and inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly when D-cycloserine was added to clozapine in dosages of 5 mg, 15 mg, 50 mg, and 250 mg consecutively for 2 weeks no changes were found (Goff et al 1996). Interestingly, 250 mg D-cycloserine daily, in addition to typical antipsychotics, was found to exacerbate psychotic symptoms, such as hallucinations, conceptual disorganization, and aggressive behavior in four of seven schizophrenic patients, although one patient with predominantly negative symptoms showed some improvement (Cascella et al 1994). Moreover, the treatment of 10 psychotic patients with D-cycloserine in dosages between 500 mg and 3000 mg daily induced an exacerbation of hallucinations and paranoia in seven patients (Simeon et al 1970).…”
mentioning
confidence: 94%
“…In contrast, it has been shown that at doses of 100 mg/day or 250 mg/day D-cycloserine had no effect on negative symptoms and worsened positive symptoms of psychosis. This may be explained by the evidence that at higher concentrations D-cycloserine acts as an antagonist rather than a partial agonist at the glycine site (Cascella et al 1994;van Berckel et al 1999). Finally, it has been suggested that glycine may be less effective when combined to clozapine than when combined to conventional neuroleptics (Evins et al 2000).…”
Section: N-methyl-d-aspartate Receptor Hypofunction Has Been Suggestementioning
confidence: 99%
“…41 Preliminary evidence has indicated that the appropriate dose of cycloserine for the treatment of schizophrenia is in the range of 50 to 100 mg/day. [40][41][42] Larger doses of 250 mg/day and 1 g/day have been associated with anxiety, irritability, and depression. 43,44 Cycloserine may be contraindicated in combination with clozapine.…”
Section: Treatment Concerns For Patients With Comorbid Depression and Tbmentioning
confidence: 99%